No significant Alpine tectonic overprint on the Cimmerian Strandja Massif (SE Bulgaria and NW Turkey). Issue 4 (12th March 2018) - Cattò, Silvia; Cavazza, William; Zattin, Massimiliano; Okay, Aral I.
ABSTRACT: We provide the first comprehensive picture of the thermochronometric evolution of the Cimmerian Strandja metamorphic massif of SE Bulgaria and NW Turkey, concluding that the bulk of the massif has escaped significant Alpine-age deformation. Following Late Jurassic heating, the central part of the massif underwent a Kimmeridgian-Berriasian phase of relatively rapid cooling followed by very slow cooling in Cretaceous-to-Early Eocene times. These results are consistent with a Late Jurassic–Early Cretaceous Neocimmerian (palaeo-Alpine) phase of north-verging thrust imbrication and regional metamorphism, followed by slow cooling/exhumation driven by erosion. From a thermochronometric viewpoint, the bulk of the Cimmerian Strandja orogen was largely unaffected by the compressional stress related to the closure of the Vardar–İzmir–Ankara oceanic domain(s) to the south, contrary to the adjacent Rhodopes. Evidence of Alpine-age deformation is recorded only in the northern sector of the Strandja massif, where both basement and sedimentary rocks underwent cooling/exhumation associated with an important phase of shortening of the East Balkan fold-and-thrust belt starting in the Middle–Late Eocene. Such shortening focused in the former Srednogorie rift zone because this area had been rheologically weakened by Late Cretaceous extension.